2004
DOI: 10.1111/j.1349-7006.2004.tb03240.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel fusion gene in a pre‐B acute lymphoblastic leukemia with t(1;19)(q23;p13)

Abstract: The most common nonrandom translocation found among childhood pre-B acute lymphoblastic leukemias (ALL) is t(1;19)(q23;p13), which frequently results in fusion of E2A with PBX1. However, rare cases of childhood ALL and various other hematological diseases with t(1;19) lack the E2A-PBX1 fusion. Analyzing a cell line with pre-B-cell phenotype, TS-2, that carries t(1;19)(q23;p13) but lacks the E2A-PBX1 fusion, we successfully cloned the breakpoints, which fell within introns of MEF2D and DAZAP1. Both chimeric tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…4 We observed that DAZAP1 protein, which did not induce anchorage-independent growth, consistently accumulated to very high levels relative to DAZAP1/MEF2D and MEF2D/DAZAP1 fusion proteins Cooperative transformation by MEF2D/DAZAP1 and DAZAP1/MEF2 V Prima and SP Hunger (Figure 1c). It was unclear whether this was because of more efficient transcription/translation, enhanced stability or reduced toxicity of the protein.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…4 We observed that DAZAP1 protein, which did not induce anchorage-independent growth, consistently accumulated to very high levels relative to DAZAP1/MEF2D and MEF2D/DAZAP1 fusion proteins Cooperative transformation by MEF2D/DAZAP1 and DAZAP1/MEF2 V Prima and SP Hunger (Figure 1c). It was unclear whether this was because of more efficient transcription/translation, enhanced stability or reduced toxicity of the protein.…”
Section: Resultsmentioning
confidence: 83%
“…14 The location of MEF2D at the breakpoint of a chromosome translocation in human acute lymphoblastic leukemia, 4,5 and the current studies demonstrating potent transforming properties of both resultant MEF2D protein chimeras establish that MEF2D has latent oncogenic properties. Members of MEF2 protein family interact with a variety of other Cooperative transformation by MEF2D/DAZAP1 and DAZAP1/MEF2 V Prima and SP Hunger proteins involved in transcriptional regulation including histone deacetylases, p300 and Cabin1/Cain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of both MEF2C and MEF2D occurs in lymphocytes, while that of MEF2C is restricted to B-cells, implying that activation in T-ALL cells may require dysregulation. 43 In pre-B-ALL, t(1;19)(q23;p13) results in the fusion of MEF2D with DAZAP1 shown to be involved in pathogenesis, 44,45 supporting the notion of leukemic potential among MEF2-proteins.…”
Section: Nkx2-5 Activates Mef2cmentioning
confidence: 97%
“…It is now essential to establish whether alterations of the class IIa HDAC-MEF2 axis occur in these human pathologies. Genetic alterations of MEF2 family members have been linked to cardiovascular diseases (Wang, 2005;Visvikis-Siest and Marteau, 2006) and acute lymphoblastic leukemia (Yuki et al, 2004;Prima et al, 2005). Similarly, alterations of MEF2 transcriptional activity have been implicated in neurodegenerative disorders (Camins et al, 2006) and cardiac hypertrophy (Czubryt and Olson, 2004).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%